Formulation and Stability Test of Physical Quality of Lotion Preparations from Moringa Oleifera L. Leaf Extract with Various Concentrations of Emulsifier TEA - Selvi Mutia, Andi; Jumain, Jumain; Arisanty, Arisanty (Indonesian Health Journal, 2023)
The tendency to use herbal ingredients has entered the world of beauty leading to increased research on cosmetic and plant formulations used to be cosmetic active substances. There are many plants that can be used, one of which is the Moringa plant which is considered sacred because it has many benefits. This study aims to determine whether Moringa leaf extract with variations in TEA concentrations of 2.5%, 3%, and 3.5% is formulated into lotions to produce an effective, stable, and safe cream. This type of research is experimental; physical quality testing is carried out before and after the storage conditions are accelerated (Freeze-thaw), including organoleptic tests, homogeneity tests, viscosity tests, pH tests, dispersion tests, and emulsion type tests. Moringa Leaf Extract can be formulated into lotion preparations with variations in TEA concentrations of 2.5%, 3%, and 3.5%. The results of the physical quality test show that all formulas meet the requirements of physical qualification. Third, the dosage formulation of Moringa leaf extract lotion (Moringa oleifera L.) with variations in TEA emulsifying concentrations of 2.5%, 3%, and 3.5% based on physical quality stability tests all meet the requirements.